The Effect of Using Learning Media in Islamic Religious Education (PAI) Learning on Student Learning Achievement in Madrasah Tsanawiyah (MTs) Nahdlatul Wathon (NW) Teros, Indonesia - Baiq Hadia Martanti (Tinta Emas Institute, 2024)
This research aims to investigate the influence of interest in learning and the level of provision of learning media on the learning achievement of class VII students at Madrasah Tsanawiyah (MTs) Nahdlatul Wathon (NW) Teros. A survey method with an associative explanatory approach was used in this research, using quantitative data to analyze causal variable relationships. The population consisted of 91 class VII students, with the entire population being sampled because the number was less than 100. The research results show that interest in learning and learning media significantly influence student learning achievement. Interest in learning and learning media contributed 70.4% to student learning achievement, while other factors such as teacher ability, student ability, and family conditions contributed 29.6%. The implications of this research emphasize the importance of increasing students' interest in learning and ensuring the availability of adequate learning media in schools. Efforts to improve learning outcomes must also pay attention to other supporting factors such as increasing teacher capabilities and family support.